Transferência de energia sem fio por indução eletromagnética - IPT: contribuições para a maximização do rendimento - Scortegagna, Renato Gregolon (2022)
With the growing demand for mobile devices, robots, drones, and electric vehicles, the recharge of the batteries of these devices with wireless power transfer is a current topic of research at a global level. This work is approached techniques that aim to increase the efficiency of the inductive power transfer (IPT). In this context, a series-parallel resonant IPT prototype was built with 100 W of nominal power. At 1 cm distance, using the proposed iterative design tuning method, the overall measured efficiency was 94%, an increase of 2.9% compared to the capacitor specification methods by equation. A novel self-driving circuit for a current-doubler synchronous rectifier is proposed using only auxiliary windings in the existent rectifier output filter inductors to drive active switches. It does not require any processing, analog circuits, gate driver circuits, or current measurement to keep itself synchronized with the resonant circuit and may be used in Si or SiC MOSFETs that support symmetrical command voltage. Experimental verification of synchronous rectifier reached the maximum overall efficiency of 94.8%. As a proposal for application in a remote UAV charging station, the prototype of the IPT system was integrated with a battery and a photovoltaic module through a Three-Port converter, whose operation was divided into Mode 1, Mode 2, and 3 Mode. In the Mode 1, power is transferred from the battery to the IPT system by phase-shift modulation under constant frequency. The IPT system load parameters control is performed from the input power, and the load voltage is feedback through wireless communication. In the power transfer from the PV module to the battery, Mode 2, the full-bridge converter operates as a parallel boost using the ZVRT technique (Zero-Voltage Resonant-Transition) with frequency modulation, obtaining soft-switching and efficiency of 96.25% at maximum power. The 3 Mode comprises the simultaneous power transfer between the three ports. The IPT system is controlled by phase-shift modulation under constant frequency. In contrast, the power flow between the PV module and the battery is controlled by the duty cycle of PWM modulation. An auxiliary inductor was added between the converter arms for soft-switching and was used asymmetrical current control in the boost inductors. This control technique allowed the operation of both converter arms under the same soft-switching threshold. It increased the auxiliary inductor by about four times and reduced conduction losses. Experimental results of the Three-Port converter under nominal power resulted in an overall efficiency of 92.2% in DISO mode (Double Input Single Output), and of 93.7%, in SIDO mode (Single Input Double Output).